At the Edges of the Welfare State: When Front-Line Bureaucrats Meet Migrant Roma Beggars in Norway - Silje Andresen; Jon Horgen Friberg (Nordic Journal of Migration Research)
Romanian Roma who beg and perform street work represent the most visible and acute form of poverty in today’s Norway, but as EU citizens operating outside formal labour markets, they have limited access to social rights and services. Using a street-level bureaucracy perspective, we explore how front-line workers in Norway’s welfare system respond to their needs, on the basis of 21 in-depth interviews with employees in non-governmental organization (NGOs), the labour and welfare services, healthcare services and municipal outreach services in Oslo and Bergen. We find that front-line workers have very limited space for discretion when interacting with this group, but when discretionary space does become available – often when interpreting the distinctions between ‘acute’ and ‘regular’ needs – many are willing to bend the rules in favour of the migrants. Their ability and willingness to do so is shaped by institutional factors, including professional ethics, administrative organization, organizational cultures and public social frames. We contribute to the literature on welfare bordering, by providing additional nuance to the understanding of the role of frontline workers in the welfare state when encountering marginalized groups such as migrant beggars.